Cyclosporine A attenuates apoptosis and necrosis after ischemia-reperfusion-induced renal injury in transiently hyperglycemic rats - de Lemos Neto, Sylvio Valença [UNESP] (2017)
Purpose: To investigate the effects of cyclosporine A on renal ischemia-reperfusion injury during transient hyperglycemia in rats. Methods: In a model of ischemia-reperfusion-induced renal injury and transiently induced hyperglycemia by intraperitoneal injection of glucose, 2.5 g.kg-1, Wistar rats were anesthetized with either isoflurane or propofol and received intravenous cyclosporine A, 5 mg.kg-1, five minutes before reperfusion. Comparison groups were isoflurane and propofol sham groups and isoflurane and propofol ischemia-reperfusion-induced renal injury. Renal tubular cell viability was quantitatively assessed by flow cytometry after cell culture and classified as early apoptosis, necrotic cells, and intact cells. Results: Early apoptosis was significantly higher in isoflurane and propofol anesthetized animals subjected to renal ischemia-reperfusion injury when compared to both cyclosporine A treated and sham groups. Necrosis percentage was significantly higher in propofol-anesthetized animals subjected to renal ischemia-reperfusion injury. The percentage of intact cells was lower in both, isoflurane and propofol anesthetized animals subjected to renal ischemia-reperfusion injury. Conclusion: In a model of ischemia-reperfusion-induced renal injury, cyclosporine A, 5 m.kg-1, administered five minutes before renal reperfusion in rats with acute-induced hyperglycemia under either isoflurano or propofol anesthesia, attenuated early apoptosis and preserved viability in renal tubular cells, regardless of the anesthetic used.